196 Paediatric Cardiomyopathy (PC); The Validation, Implementation and Utility of a 71 Gene NGS Diagnostic Panel to Detect Variants in Rare Cardiac Genes. (6th June 2015) - Gable, Mary; Honeychurch, Julie; Sawyer, Hilary; Newbury-Ecob, Ruth; Steward, Colin; Robert, Leema; Bueser, Tootie; Gardiner, Carol; Bowen, Claire; Williams, Maggie
Abstract : Paediatric cardiomyopathy (PC) has multiple genetic causes and can present in infancy with cardiac failure and sudden death. Within the Bristol Genetics Laboratory analysis of Barth Syndrome ( TAZ gene) is triggered by an abnormal cardiolipin ratio, but only 7% of referred cases are mutation positive. Next generation sequencing technology enables large sets of related genes to be analysed simultaneously. As considerable clinical and genetic heterogeneity exists within and between PC families, a one off cost-effective gene panel test helps diagnosis and elucidates complex clinical presentations. An Agilent SureSelect custom enrichment kit was designed to include 71 paediatric cardiomyopathy genes, with data analysis through an in-house bioinformatics pipeline (Broad Institute) and Geneticist Assistant (SoftGenetics). This assay has been validated and introduced into service as a United Kingdom Genetic Testing network (UKGTN) approved test. Validation involved two runs using 17 patients, including 14 with known pathogenic variants with100% concordance. The assay coverage at 30x was close to the predicted 99.7% at design with one exonic gap ( CTF1, exon 3). Since introduction into service 37 patients have been tested, including infantile/paediatric cases; patients negative for other genes and patients who have phenotypic incompatibility with their reported pathogenic variant where digenic inheritance is suspected. 32/37 (86%) patients have at least one potentially pathogenic variant. In onefamily with HCM, a MYBPC3 variant c.1505G >A, p.(Arg502Gln) and a previously reported NEBL pathogenic variant c.180G >C, p.(Lys60Asn) (nebulette protein) were detected in a severely affected male demonstrating that multiple variants can explain phenotypic severity. The utility of testing rare genes is exemplified by: 1) A teenager with LV dilation and FH of sudden death who was heterozygous for a RMB20 ( RNA binding protein) variant c.1907G >A, p.(Arg636His), previously reported with severe familial DCM; 2) a patient with congenital heart block, LV dilation and FH was heterozygous for a novel likely pathogenic MYH6 (alpha heavy chain subunit) variant c.3578C >T, p.(Ala1193Val). Furthermore, a novel heterozygous TTN A-band frameshift variant was identified in an infantile DCM patient; recent data suggests TTN frameshift variants have not been reported in infantile cardiomyopathy. Details of the validation of this technology, an audit of this patient cohort illustrated by interesting cases will be presented.